Dynamic of Migration lifestyle and settlement of nomad in Bali, Indonesia - Wibowo, Tangguh Okta (Indonesian Journal of Geography, 2024)
This research highlights the lifestyle of digital nomads, which is becoming a more common lifestyle in today's digital age. Bali is one of the most popular destinations for nomads. This research aims to explore the motivations of digital nomads in Bali. The research uses the case study research method by mapping several informants as research subjects. This article discusses the experiences of foreign tourists in Bali, particularly digital nomads, and the migratory lifestyle. It explores conversations and perspectives on Bali's attractiveness, working life, cultural interaction, and modern mobility. The findings show that the concept of 'nomad' is associated not only with high levels of mobility, but also with individuals who have chosen to settle in Bali due to finding the culture and lifestyle appealing. Modern mobility reflects the search for meaning in one's life experiences, which may include a search for stability and a depth of experience in one place. Furthermore, the discussion examines that the emergence of Bali's digital nomad community brings both economic benefits and challenges of overtourism on local communities.